Online-based Literacy Test Instruments for Evaluating Prospective Elementary School Teachers’ Science Competencies - Wiyoko, Tri; Wulandari, Titis; Irhas, Muhammad (Universitas Pendidikan Ganesha, 2024)
The Minimum Competency Assessment is used to measure school performance based on literacy and numeracy. In this regard, it is necessary for prospective elementary school student educators to train and master scientific literacy competencies. This research aims to produce an online-based literacy test instrument for assessing the science competency of elementary school teacher education students. This type of research is research and development. The procedure for developing literacy test instruments uses the 4D model (Define, Design, Development and Discussion). This research involved 3 validators and empirical test subjects consisting of 30 Prospective Elementary School Teachers. Data collection uses needs analysis sheets, language validation sheets, materials and graphics. Next, empirical validity is carried out using the Quest program to determine the level of difficulty (Thresholds) and suitability of the items (Outfit-t). The results of the test question instrument validation show that 89.5% of the material validation is in the very good category, 92% of the language validator is in the very good category, 96.5% of the graphic validator is in the very good category. The distribution of questions that have been developed shows that students' ability to identify scientific issues is 66% in the medium category, 65% in explaining scientific phenomena is in the medium category and the ability to use scientific evidence is 45% in the very low category. So the test question instrument developed meets the validity of the material, language, graphics and empirical validity, so it is suitable to be used to measure students' scientific literacy competency.